2010
DOI: 10.3945/jn.109.116020
|View full text |Cite
|
Sign up to set email alerts
|

Soy Product and Isoflavone Intakes Are Associated with a Lower Risk of Type 2 Diabetes in Overweight Japanese Women

Abstract: Isoflavones have been shown to improve glucose metabolism, but epidemiologic data are limited. We prospectively investigated the relationship between soy product and isoflavone intake and the risk of developing type 2 diabetes among Japanese adults. Participants were 25,872 men and 33,919 women aged 45-75 y, who participated in the second survey of the Japan Public Health Center-Based Prospective Study and had no history of diabetes. Soy product and isoflavone intakes were ascertained using a 147-item FFQ. Odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
101
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 29 publications
5
101
3
Order By: Relevance
“…The average daily intake of the reference group (Q1) in our study population was 23·5 g/d, which corresponds to high levels in other populations (22,24) ; only two participants consumed 3 g/d, which was classified as 'high' consumption associated with lower glucose intolerance rates in one previous study (22) . Only one published study on legumes showed intake greater than the current study population in the reference group (29 g/d in the lowest quintile), in which the authors also reported no association between legumes (soya) intake and type 2 diabetes in Japanese women (25) . This may partly explain why we observed inverse associations in only the highest tertiles of carbohydrate, protein, fat and sugar consumption, where these participants' legume consumption was significantly higher (P < 0·0001; data not shown) than in the lowest tertiles; we also found higher mean legume intake in persons of lower BMI compared with those of higher BMI (P = 0·02; data not shown).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The average daily intake of the reference group (Q1) in our study population was 23·5 g/d, which corresponds to high levels in other populations (22,24) ; only two participants consumed 3 g/d, which was classified as 'high' consumption associated with lower glucose intolerance rates in one previous study (22) . Only one published study on legumes showed intake greater than the current study population in the reference group (29 g/d in the lowest quintile), in which the authors also reported no association between legumes (soya) intake and type 2 diabetes in Japanese women (25) . This may partly explain why we observed inverse associations in only the highest tertiles of carbohydrate, protein, fat and sugar consumption, where these participants' legume consumption was significantly higher (P < 0·0001; data not shown) than in the lowest tertiles; we also found higher mean legume intake in persons of lower BMI compared with those of higher BMI (P = 0·02; data not shown).…”
Section: Discussioncontrasting
confidence: 67%
“…T1 T2 T3 T1 T2 T3 T1 T2 T3 T1 T2 T3 T1 T2 T3 M The epidemiological data focusing on legumes specifically showed inverse associations between legumes and diabetes in some (22)(23)(24)(25)(26)30) but not all (25,(27)(28)(29)31) studies, including one population-based study in India reporting an inverse association between legume intake and selfreported diabetes (30) . The authors were restricted to National Family Health Survey-3 questions on frequency intake without quantitative measures, were unable to control for total energy intake (which is correlated with legume intake) or other confounders, such as physical activity and assessed self-reported diabetes, which may be subject to temporal ambiguity of diabetic patients increasing legume intake as a result of their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumption of soya foods (tofu and other soya products) was previously associated with a significantly reduced prevalence of glycosuria in 39 385 Chinese women aged 40-70 years without diabetes, especially postmenopausal women with BMI < 25 kg/m 2 (15) . Nanri et al reported a significant correlation between soya products and daidzein intake and a reduced cumulative incidence of type 2 diabetes among women with BMI > 25 kg/m 2 and postmenopausal women (16) . In a prospective study in China, Villegas et al reported that the consumption of legumes and soya foods was associated with a decreased risk of type 2 diabetes in 64 227 women aged 40-70 years (17) .…”
Section: Discussionmentioning
confidence: 99%
“…An inverse association between soya food intake and the prevalence of glycosuria was also reported in postmenopausal non-obese Chinese women (15) . Furthermore, a recent prospective study in Japan showed that higher intake of soya products and isoflavones was associated with a decreased odds ratio of diabetes among overweight or postmenopausal women (16) . The consumption of some soya foods was inversely associated with the risk of type 2 diabetes among Asians in two prospective studies (17,18) .…”
mentioning
confidence: 99%